Reintroduction strategy for the Andean Condor Conservation Program, Argentina. Issue 1 (31st October 2016) - Astore, V.; Estrada, R.; Jácome, N. L.
Abstract : The Andean condor Vultur gryphus is the largest bird in the world with flight capacity. For thousands of years the Andean condor has been honoured as a sacred link between space and humans by indigenous communities. In the last 100 years, the range of this emblematic species contracted rapidly and the Andean condor was pronounced extinct at both ends of its endemic South American range, in Venezuela and on the Atlantic coast of Patagonia. The Andean condor appears in Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora and is listed as in 'Danger of Extinction' by the United States Fish and Wildlife Service. In addition, according to the International Union for Conservation of Nature, this species is classified as Near Threatened. In 1991, the Andean Condor Conservation Program (PCCA: Programa Conservación Cóndor Andino) was founded in Argentina. The PCCA started by performing genetic analyses and documenting the condor population in zoological institutions in a Latin American regional studbook. The PCCA then developed artificial‐incubation programmes and techniques for hand rearing birds without human contact, and worked to rescue and rehabilitate wild condors. The PCCA has succeeded in rearing 57 chicks and rescuing 197 wild condors. This paper describes the strategy used by the PCCA to reintroduce 160 condors throughout South America. Abstract : The Andean condor Vultur gryphus is the largest bird in the world with flight capacity. In 1991, the Andean Condor Conservation Program (PCCA: Programa Conservación Cóndor Andino) was founded in Argentina. The PCCA started by performing genetic analyses and documenting the condor population in zoological institutions. Using a system of specifically developed artificial‐incubation programmes and techniques for hand rearing birds without human contact, in tandem with work to rescue and rehabilitate wild condors, the PCCA has succeeded in rearing 57 chicks and rescuing 197 condors from the wild. This paper describes the strategies used by the PCCA to reintroduce 160 Andean condors, both captive‐bred and rehabilitated wild birds, throughout South America. (Photo: Silvia Peralta, Fundación Bioandina Argentina)